Analisis Kualitas Sauerkraut (Asinan Jerman) dari Kol (Brassica oleracea) selama Fermentasi dengan Variasi Konsentrasi Garam - Rahmah Hayati; Rahmat Fadhil; Raida Agustina (Department of Agricultural Engineering, Syiah Kuala University, 2017)
Quality Analysis of Sauerkraut (Pickle of German) from Cabbage (Brassica oleracea) during Fermentation with Salt Concentration VariatioAbstract. Cabbage (Brassica oleracea) is a vegetable that many contain vitamin, carbohydrate, protein and mineral. Cabbage has a limited storage age because the high water content so easily damaged and not durable. Cabbage can be preservedby fermentation process into sauerkraut (pickle of German) to produce with especially characteristic flavor and taste. The research aims to analysis of quality sauerkraut with salt concentration variation during fermentation. Parameters analysed was physical characteristic, chemical analysisand organoleptic test. The value obtained is processed using analysis of variance (ANOVA) at a significant levelP0,05. The factor tested is salt concentration variation composed for2,25% (Control), 2,5%, 7,5% and 12,5%. This research result is indicated of sauerkraut, there are the best experiment is the salt concentration of 2,5% and 2,25%. The mean of value salt concentration of 2,25% is weight loss 20,75%, pH 3,56; TSS 7,75%, vitamin C 7,41 mg/100gr, water content 90,93%, activity water (Aw) 0,245 and lactid acid 0,0096%. While the mean of value salt concentration of 2,5% is weight loss 20,05%, pH3,69; TSS 7,55%, vitamin C 13,15 mg/100gr, water content 92,104%, Aw 0,245 and lactid acid 0,0095%. Saltconcentration variation in sauerkraut found to be significant on TSS, weight loss, water content, lactid acid, flavor, color, taste, texture and overall acceptance of sauerkraut. But it has non-significant on pH, vitamin C andAw sauerkraut. Based in organoleptic test result all experiment sauerkraut interested by Panelists is the product concentraced sauerkraut of 2,25% and 2,5%.